Renal developmental genes are differentially regulated after unilateral ureteral obstruction in neonatal and adult mice - Kubik, Melanie Jennifer; Wyczanska, Maja; Gasparitsch, Mojca; Keller, Ursula; Weber, Stefanie; Schaefer, Franz; Lange-Sperandio, Bärbel (Scientific reports, 2020)
Congenital obstructive nephropathy hinders normal kidney development. The severity and the duration of obstruction determine the compensatory growth of the contralateral, intact opposite kidney. We investigated the regulation of renal developmental genes, that are relevant in congenital anomalies of the kidney and urinary tract (CAKUT) in obstructed and contralateral (intact opposite) kidneys after unilateral ureteral obstruction (UUO) in neonatal and adult mice. Newborn and adult mice were subjected to complete UUO or sham-operation, and were sacrificed 1, 5, 12 and 19 days later. Quantitative RT-PCR was performed in obstructed, intact opposite kidneys and sham controls for Gdnf, Pax2, Six4, Six2, Dach1, Eya1, Bmp4, and Hnf-1β. Neonatal UUO induced an early and strong upregulation of all genes. In contrast, adult UUO kidneys showed a delayed and less pronounced upregulation. Intact opposite kidneys of neonatal mice revealed a strong upregulation of all developmental genes, whereas intact opposite kidneys of adult mice demonstrated only a weak response. Only neonatal mice exhibited an increase in BMP4 protein expression whereas adult kidneys strongly upregulated phosphatidylinositol 3 kinase class III, essential for compensatory hypertrophy. In conclusion, gene regulation differs in neonatal and adult mice with UUO. Repair and compensatory hypertrophy involve different genetic programs in developing and adult obstructed kidneys.